Hypertension among people living with HIV/AIDS in Cameroon: A cross-sectional analysis from Central Africa International Epidemiology Databases to Evaluate AIDS - Dzudie, Anastase; Hoover, Donald; Kim, Hae-Young; Ajeh, Rogers; Adedimeji, Adebola; Shi, Qiuhu; Pefura Yone, Walter; Nsame Nforniwe, Denis; Thompson Njie, Kinge; Pascal Kengne, Andre; Ebasone, Peter Vanes; Barche, Blaise; et al. (PloS one, 2021)
Antiretroviral therapy (ART) success has led people to live longer with HIV/AIDS (PLWH) and thus be exposed to increasing risk of cardiovascular diseases (CVD). Hypertension (HTN), the biggest contributor to CVD burden, is a growing concern among PLWH. The current report describes the prevalence and predictors of HTN among PLWH in care in Cameroon. This cross-sectional study included all PLWH aged 20 years and above who received care between 2016 and 2019 at one of the three Central Africa International Epidemiology Databases to Evaluate AIDS (CA-IeDEA) sites in Cameroon (Bamenda, Limbe, and Yaoundé). HTN was defined as blood pressure (BP) [greater than or equal to]140/90 mm Hg or self-reported use of antihypertensive medication. Logistic regressions models examined the relationship between HTN and clinical characteristics, and HIV-related factors. Among 9,839 eligible PLWH, 66.2% were women and 25.0% had prevalent HTN [age-standardized prevalence 23.9% (95% CI: 22.2-25.6)], among whom 28 (1.1%) were on BP lowering treatment, and 6 of those (21.4%) were at target BP levels. Median age (47.4 vs. 40.5 years), self-reported duration of HIV infection (5.1 vs 2.8 years years), duration of ART exposure (4.7 vs 2.3 years), and CD4 count (408 vs 359 cell/mm.sup.3) were higher in hypertensives than non-hypertensives (all p<0.001). Age and body mass index (BMI) were independently associated with higher prevalent HTN risk. PLWH starting ART had a 30% lower risk of prevalent HTN, but this advantage disappeared after a cumulative 2-year exposure to ART. There was no significant association between other HIV predictive characteristics and HTN. About a quarter of these Cameroonian PLWH had HTN, driven among others by age and adiposity. Appropriate integration of HIV and NCDs services is needed to improve early detection, treatment and control of common comorbid NCD risk factors like hypertension and safeguard cardiovascular health in PLWH.